Finanse gmin w świetle nowej ustawy o zagospodarowaniu przestrzennym - Maciejasz-Świątkiewicz, Marta (Funds of Districts in the Light of the New Law on Space Planning, 2005)
This article presents the problem of space planning and its influence at municipal budgets. There are presented statutory regulations' changes and their financial consequences. Basing on the results of the Highest Chamber of Control's and Housing Economy Institute's inspections, the article presents how space planning influences Polish municipal budgets.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 26-33